血管内皮細胞株 bEnd.3 細胞の過酸素水素誘発細胞死に対するアペリンの保護作用 - 石丸, 侑希; 藤原, 彩華; 乗松, 愛美; 前田, 定秋; 山本, 時駆; 藤原, 慧; 吉岡, 靖啓; 山室, 晶子 (日本薬理学会年会要旨集, 2019)
Apelin plays an important role in the proliferation of vascular endothelial cells, and the expression of apelin is enhanced after ischemic stroke. Since the production of reactive oxygen species (ROS) including hydrogen peroxide (H2O2) is elevated in the post-ischemic brain, the proliferated endothelial cells are subjected to oxidative stress. However, the effects of apelin on oxidative stress-induced injury in endothelial cells are poorly investigated. In this study we investigated the effect of apelin on H2O2-induced cell death in mouse endothelial cell line bEnd.3. Cell viability was determined by a colorimetric 3,4,5-dimethylthiazol-2-yl-2,5-diphenyl tetrazolium bromide (MTT) assay, and intracellular ROS levels were evaluated by dihydroethidium (DHE) staining. Treatment of bEnd.3 cells with H2O2 (150 µM) increased DHE-positive cells and induced cell death. Pretreatment with [Pyr1]-apelin-13 (10 µM) for 24 h reduced the increase in the number of DHE-positive cells and attenuated the cell death. These results suggest that apelin protects bEnd.3 cells from H2O2-induced cell death by decreasing the intracellular ROS levels.